Implementasi Sistem Informasi Akuntansi Persediaan Obat-Obatan Pada Rumah Sakit PKU Muhammadiyah Gamping Sleman-D.I. Yogyakarta - Sofia Nur Arifin Maulana; Diska Arliena Hafni (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2021)
This study aims to analyze the accounting information system for drug supplies at PKU Muhammadiyah Gamping Hospital. The employed research method was descriptive qualitative research. Data sources were from secondary and primary data. Based on the results of the study, it can be concluded that the accounting information system for drug supplies at PKU Muhammadiyah Gamping Hospital has been running well because the existing system can provide the required information. However, there are still weaknesses; namely, the physical activity is not maximal; the warehouse stock card does not include an expiration date. In addition, the hospital has not made 4 copies of an official report on the drug disposal following the Minister of Health Regulation (Permenkes) Number 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies.